2012
DOI: 10.2136/sssaj2012.0129
|View full text |Cite
|
Sign up to set email alerts
|

Soil Drainage Class Influences on Soil Carbon in a New England Forested Watershed

Abstract: Imperfectly drained soils under forests can occupy extensive areas of the landscape and understanding how they might differ from upland forest soils can be critical for understanding soil organic carbon (SOC) across forested landscapes. Research on forest SOC across drainage gradients has been limited. This research was a case study at the Bear Brook Watershed in Maine (BBWM), a long‐term ecological research site, that focused on SOC pools and fluxes across three soil drainage classes (moderately well drained‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…However, Figure 2a and 2b shows that in the SSURGO database there were no significant differences in SOC density among PD, SPD, WMD, and WD soils at 0-20 cm and 0-100 cm depth increments. Raymond et al (2012) reported similar results from their studies in a forested watershed in Maine. They concluded that illuvial accumulations of SOC combined with greater belowground SOC inputs from roots enhanced total SOC accumulations in MWD soils.…”
Section: Soil Drainage Class and Socsupporting
confidence: 70%
See 1 more Smart Citation
“…However, Figure 2a and 2b shows that in the SSURGO database there were no significant differences in SOC density among PD, SPD, WMD, and WD soils at 0-20 cm and 0-100 cm depth increments. Raymond et al (2012) reported similar results from their studies in a forested watershed in Maine. They concluded that illuvial accumulations of SOC combined with greater belowground SOC inputs from roots enhanced total SOC accumulations in MWD soils.…”
Section: Soil Drainage Class and Socsupporting
confidence: 70%
“…In contrast, approximately 54% of VPD soils in the SSURGO database were Histosols, and the rest were Inceptisols (38%), Entisols (7%), and Spodosols (1%) (Supplemental Table S1). Maine Inceptisols are often characterized as forested mineral wetland soils and have much lower SOC than Histosols, at least partly due to the extended aerobic periods at the soil surface that facilitate SOM decomposition (Raymond, Fernandez, & Simon, 2012). Results from the PCA analysis in Supplemental Table S2 shows that all SSURGO attributes studied (i.e., soil order, drainage class, parent material, and texture) influence SOC density, and illustrates the relative strengths of each factor in the determination of SOC density among the databases.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for the 40 to 100 cm depth increment, C concentration at the Howland Forest was approximately 1.37% compared with 0.30%, 0.27%, and 0.24% for the selection, shelterwood, and commercial clearcut treatments on the PEF. Other studies have reported higher average mineral soil C stocks for sites in Maine (Birdsey and Lewis 2003;McLaughlin and Phillips 2006;Fernandez 2008;Raymond et al 2013).…”
Section: Discussionmentioning
confidence: 90%
“…For instance, Raymond et al (2013) found that mineral soil C stocks were greater in moderately well-drained soils than more poorly drained soils in a coniferous forest. However, Richardson and Stolt (2013) did not find significant differences in C stocks between well-drained and moderately well-drained soils in southern New England.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation